Al-Qur'an STUDI ANALISIS TERHADAP IMPLEMENTASI PEMBELAJARAN TAJWID PADA SISWA SEKOLAH DASAR DI ERA PANDEMI COVID 19: Persiapan dan Perencanaan Pembelajaran Tajwid Secara Daring, Pelaksanaan Pembelajaran Tajwid Secara Daring, Evaluasi Pembelajaran Tajwid Secara Daring - Faradina Nur Setianingsih; Fifin Al Fionita; Istiani Nur Kasanah; Yusuf Hanafiah (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2021)
This study describes and analyzes the implementation of tajwid learning for Sogan Elementary School students during the Covid-19 pandemic era. Where the purpose of this study is to analyze the implementation of recitation learning in improving students' recitation skills at SDN Sogan. Tajweed learning at SDN Sogan is carried out online, considering the increase in cases of being infected with the Covid-19 virus in Kulon Progo Regency and in accordance with recommendations from the government in order to create comfort and safety in the learning process. This study uses a descriptive analysis method using a qualitative approach, which describes the use of media in learning during the Covid-19 pandemic era. Based on the results of interviews conducted by researchers, learning recitation is carried out using online methods, namely by using digital media platforms such as Whatsapp, Youtube and Google forms. These platforms can facilitate the delivery of tajwid learning so as to create good learning objectives. This can be seen from the stages in learning recitation by using the online method. Starting from preparation and planning that is quite mature with the administration of learning planning, preparation in terms of the capacity of educator resources, as well as preparation of supporting facilities and infrastructure for recitation learning in the pandemic era. Furthermore, it can also be seen from the evaluation of learning held in Tajweed learning using the online method that went quite well. Keywords: Implementation, Tajweed Learning, Covid-19 Pandemic